Complicated migraine resulting in blindness due to bilateral retinal infarction. Issue 3 (March 1992) - Glenn, A M; Shaw, P J; Howe, J W; Bates, D
Abstract : Retinal migraine is not uncommon, but permanent sequelae in the anterior visual pathway are rare. We describe the case of a young woman in whom blindness developed over a six-year period due to recurrent episodes of migraine-related occlusions of a branch retinal artery.